Book review: Copyright‘s broken promise: how to restore the law‘s ability to promote the progress of science - Maceviciute, Elena (Information Research an international electronic journal, 2023)
Willinsky, John. Copyright‘s broken promise: how to restore the law‘s ability to promote the progress of science. Cambridge, MA: The MIT Press, 2023. xii, 175 p. ISBN 978-0-262-54441-2